Molecular Identification, Geometric Morphometrics And Phylogenetic Relationship Of Commercially Important Nemipteridae From Malaysian Waters And Neighboring Seas Inferred By mtDNA And Nuclear Genes - Imtiaz, Ayesha (2018)
This study employed genetic and morphometric approaches to assess the molecular and morphometric differentiation as well as phylogenetic relationships among commercially important species of family Nemipteridae. Molecular investigations were conducted based on two mitochondrial and one nuclear genes on 210 individuals within 13 presumed species of family Nemipteridae from seven marine regions; Indian Ocean, Straits of Malacca, East South China Sea (ESCS), West South China Sea (WSCS), North South China Sea (NSCS), Sulu Sea (SS) and Celebes Sea (CS).